Interfacial Bonding Properties Experimental Research of 316L Stainless Steel–Carbon Steel Clad Rebar in the Process of Intermediate and Finish Rolling - Gaozhen Liang; Jianping Tan; Xuehai Qian; Yong Xiang; Zhe Gou; Binbin Zhang; Taili Chen (Metals, 2025)
The interfacial bonding properties of stainless steel clad (SSC) rebars determine whether they can be widely used. In the industrial production of SSC rebars, the process of intermediate and finish rolling of the microstructure evolution, element diffusion behavior, and interfacial bonding properties of bimetallic interfaces are investigated. In this paper, 316L seamless stainless steel (SS) tube and HRB400E carbon steel (CS) bar were prepared by a vacuum oxidation-free composite round billet, and the industrial emergency stopping of SSC rebars’ hot rolling was carried out. The metallographic results showed that the thicknesses of the carburized austenite zone (CAZ) varied greatly (832–238 μm) and showed a parabolic downward trend, while the thicknesses of the decarburized ferrite zone (DFZ) varied little (85–99 μm). The elemental line scans showed that Fe and Cr had the same parabolic downward trend. The intermediate-rolling had a great influence on element diffusion, and, in S6–9, the diffusion distance of Fe and Cr decreased significantly. The diffusion distances of the elements in the intermediate-rolling back stage and finishing-rolling front stage (S9–12) were basically balanced. The elemental diffusion distances and interfacial bonding strength were not consistent. Among them, the shear strength (τ) of S13 was 410.7 MPa. Compared with ordinary rebars, the yield strength (Re) and tensile strength (Rm) of finished SSC rebars were increased by 7.05% (30.9 MPa) and 7.10% (43.0 MPa), respectively. The tensile properties exceed those of mixture effects. The paper provides a theoretical basis for the improvement of the interfacial bonding strength and optimization of the rolling process system for the industrial production of SSC rebars.